Calcium Dobesilate Restores Autophagy by Inhibiting the VEGF/PI3K/AKT/mTOR Signaling Pathway - Wang, Yue; Lu, Yun-hong; Tang, Chao; Xue, Mei; Li, Xiao-yu; Chang, Yun-peng; Cheng, Ying; Li, Ting; Yu, Xiao-chen; Sun, Bei; Li, Chun-jun; Chen, Li-ming (Frontiers in Pharmacology, 2019)
Objective: Calcium dobesilate (CaD), an effective drug for the treatment of diabetic microvascular complications, especially diabetic retinopathy, is widely used in the clinic. Interestingly, several studies have indicated that CaD is therapeutic for diabetic kidney disease (DKD). Recently, evidence has indicated that altered VEGF expression and decreased autophagy are the main pathological mechanism of proteinuria. Thus, this study was conducted to explore the effect of CaD on restoring autophagy in DKD and the possible signaling pathway between VEGF and autophagy. Methods: Obese mice with spontaneous diabetes (KK-Ay) and high-fat diet- and streptozotocin-induced diabetic mice (HFD/STZ), were used in this study. Biochemical staining, western blotting and immunohistochemistry were conducted to determine the angioprotective effect of CaD and the underlying mechanism between autophagy and VEGF/VEGFR. Results: Our results showed that CaD was capable of reducing albuminuria and restoring renal histological changes in KK-Ay and HFD/STZ-induced diabetic mice. CaD restored autophagy by decreasing the protein expression of LC3 II, Atg5, and Beclin 1 and increasing the expression of P62. Moreover, CaD reduced the activation of the autophagy-related PI3K/AKT/mTOR pathway possibly via decreasing VEGF and downregulating VEGF receptor 2. Conclusion: Overall, CaD, as a novel potential therapeutic drug for DKD, plays a key role in protecting renal function and restoring autophagy by blocking VEGF/VEGFR2 and inhibiting the PI3K/AKT/mTOR signaling pathway.